KARAKTERISTIK INTELEKTUAL DAN PERADABAN BANI UMAYYAH (KUTTAB SEBAGAI PENDIDIKAN ISLAM DASAR BAGI ANAK USIA DINI) - MUHARRAHMAN RAHMAN; RIS'AN RUSLI; AMILDA SANI; DAVIK YASIN; AHMAD SUBIYADI (Raudhah - Proud To Be Professional, 2022)
Abstract The presence of Al-Qur'an study guidance is a manifestation of civilization and the development of Islamic Education. This study aims to re-describe the Kuttab Education system during the Umayyad era which is then analyzed by linking non-formal educational institutions for early childhood in the era of society 5.0, namely Al-Qur'an tutoring. The author uses a type of research library research with a descriptive analysis approach. The result is that Kuttab Education during the Umayyad era provided inspiration and contribution to Islamic Education today. Especially tutoring Al-Qur'an. Both of them have in common that lies in the material taught and the pattern of teachers who attend directly to students' homes. Al-Qur'an study guidance is present as an alternative for young children to learn to read and write the Qur'an, even other Islamic sciences.